2x+6(-2.5x+5)=-4

Simple and best practice solution for 2x+6(-2.5x+5)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6(-2.5x+5)=-4 equation:


Simplifying
2x + 6(-2.5x + 5) = -4

Reorder the terms:
2x + 6(5 + -2.5x) = -4
2x + (5 * 6 + -2.5x * 6) = -4
2x + (30 + -15x) = -4

Reorder the terms:
30 + 2x + -15x = -4

Combine like terms: 2x + -15x = -13x
30 + -13x = -4

Solving
30 + -13x = -4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + -13x = -4 + -30

Combine like terms: 30 + -30 = 0
0 + -13x = -4 + -30
-13x = -4 + -30

Combine like terms: -4 + -30 = -34
-13x = -34

Divide each side by '-13'.
x = 2.615384615

Simplifying
x = 2.615384615

See similar equations:

| (-2)x(-25)= | | x+x*x=16 | | -46=3x+7y | | x/9-5/6=4x/9 | | (X-17.7)+19.6=28.8 | | 3-2a=15 | | 7(10x+8)=-364 | | 4y+4-3y=2y-6 | | f(x)=4x^2+6x+3 | | r/3-3/8/r=-3/4 | | 6y+2(3x+5)+2y+3= | | 5(x-3)=4x-9+3x | | 5a+b=2 | | (5.6*10^-6)/(7*10^3)= | | -7x-4(5x-2)=197 | | 3x-3(x+1)=e | | 5.6*10^-6/7*10^3= | | 14x-17=6x-10 | | 5.6X10^-6/7X10^3= | | h^2+9h+8=0 | | sin^2xcos^2x=1-cos4x/8 | | 5(a-2)=3(a+1) | | 4y-25=35 | | 2mi=ft | | -2x+7y+-7y=0+-7y | | 4x-16=10x+8 | | 25-(-p+18)=45 | | 120=5x+5(-3x+10) | | 360-59-90-19x= | | 1 = z4– 3 | | h^2-14h+24=0 | | x^2+15x-8=8 |

Equations solver categories